International relations : the path not taken : using international law to promote world peace and security / Thomas J. Schoenbaum. - Schoenbaum, Thomas J. (Cambridge University Press, 2006)
This book is a comprehensive analysis of the relevance of international law to the conduct of international relations and foreign policy. Written by a distinguished international lawyer and academic with over 35 years of experience, this book contains a systematic treatment of both fields of study. This work serves as an introduction to contemporary theories of international relations and as a primer on international law especially for the non-lawyer. Focusing on contemporary problems of terrorism, nuclear non-proliferation, war and peace, economic development, protection of the global environment, reform of the United Nations, democracy and protection of human rights, this work develops the thesis that international law is a neglected tool of foreign policy that can be used to address many of today's difficult and unresolved problems. It concludes by advocating a 'new global order' in the form of the rule of law and multilateral solidarity in addressing world problems.